Industriebeschäftigung im Wandel: Arbeiter, Angestellte und ihre Arbeitsbedingungen - Thomas Haipeter; Christine Slomka (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In der Industrie findet ein kontinuierlicher Prozess der internen Tertiarisierung statt. Die Zahl der Angestellten ist inzwischen ebenso hoch wie die der Arbeiter. Der Frauenanteil unter den Angestellten stagniert allerdings. Das Niveau der prekären Beschäftigungsformen wie Befristungen, Minijobs oder Leiharbeit ist bei den Angestellten weit niedriger als bei den Arbeitern. Zugleich weisen Angestellte im Durchschnitt höhere Qualifikationen, einen höheren betrieblichen Status und höhere Einkommen auf. Dennoch sind die Arbeitsbedingungen widersprüchlich. Wichtigste Anzeichen dafür sind lange Arbeitszeiten, wachsende Arbeitsintensität und Klagen über schlechte Aufstiegschancen. Zugleich empfinden viele Angestellte ihre Arbeitsplätze als sicher. Zu den Gewerkschaften bleiben die Angestellten stärker auf Distanz, auch wenn ihr Organisationsgrad schwächer gesunken ist als derjenige der Arbeiter. Dafür ist ihr Anteil an aktiven Betriebsratsmitgliedern inzwischen höher als bei den Arbeitern. – – [Change in industrial employment - Working conditions of blue and white collar workers] Using data from the German Socio-Economic Panel (SOEP) and the German Microcensus, the paper compares the working and employment conditions of blue and white collar workers and their relation to trade unions. The aim of the paper is to develop starting points for the collective representation of white collar workers interests because employees have been less in focus in the past. In addition, our analysis shows that employees are becoming increasingly important for labour unions because the number of employees in the industry has increased while the number of workers in the direct production has decreased. Furthermore, the term 'white collar employee' has lost little of its meaning as a relevant category of social practice, although the formal distinction between workers and employees in the industry no longer exists. Our results show that employees have on average still better working and employment conditions than workers. They have higher qualifications, higher occupational status, higher incomes and they consider their employment as safer. Furthermore, precarious forms of employment such as fixed-term contracts, marginal part-time jobs (Minijob) and temporary agency work are less widespread among employees than among workers. But the working and employment conditions of white collar employees are also showing negative trends. Employees complain much more often about long working hours, increasing work intensity and a lack of career prospects than workers. Yet despite this development, white collar employees keep their distance to trade unions. However, their unionisation rate is more stable over time than the organisational degree of blue collar workers.
Keywords: 330; white collar employees; blue collar workers; Metal and Electrical Industries; Chemical Industry; Germany; working conditions; SOEP; Microcensus; working time; union membership